Edukasi Perilaku Hidup Bersih dan Sehat (PHBS) pada Siswa SDN Kopek sebagai Upaya Mewujudkan Sekolah Sehat - Kentama Inzaghi; wahyu Unggul Widodo; Agussalim; Siska Anggraini; Novita Sari; Restu Kurnia Wulan Safitri; Salsadela Mayza Sabira; Ulfa lailatul Sofia; Sindy Hertika Putri (Jurnal Pengabdian kepada Masyarakat Cahaya Negeriku, 2026)
Community service activity entitled "Education on Clean and Healthy Living Behavior (PHBS) for SDN  Kopek Students to Realize Healthy School" was conducted by targeting 50 elementary students (grades 4-5) in Kopek Village, Godong Sub-district, Grobogan Regency. This intervention aimed to enhance knowledge, skills, and motivation in proper handwashing with soap (CTPS) to give attention to poor hygiene practices contributing to infectious diseases. Methods combined interactive health education through LCD projector visualization of enlarged virus images on unclean hands, animated video demonstration of WHO's 6-step handwashing technique, knowledge assessment, guided hands-on practice, demonstration by selected students, and closure with synchronized handwashing song and movements. Results demonstrated significant improvements: students transitioned from basic awareness to better execution of CTPS procedures, exhibiting increased confidence during demonstrations and sustained engagement through mnemonic songs. Visual risk perception via virus imagery and visual-auditory-kinesthetic learning  strengthened long-term memories, confirming effectiveness of participatory approaches over conventional lectures. Findings align with social learning theory and prior studies showing 70-85% gains in handwashing compliance post-intervention.